Socially and gender-inclusive sampling of tricot participants and building horizontal partnerships with crop users - 1000FARMS Platform (2025)
This poster presents a reflection on sampling strategies used in tricot-based on-farm trials, with a focus on aligning scientific rigor with real-world implementation. It explores the balance between statistical requirements and practical field constraints, providing lessons learned from tricot trials conducted by 1000FARMS partners. The poster contributes to ongoing methodological improvements to ensure robust and inclusive data collection across diverse contexts.